Respuesta :

Answer:

y=1x+3

Step-by-step explanation:

y=kx + m

k= y2-y1 / x2- x1

pick two of them, so for example (-2,5) and (0,3)

k=(3-5)/(0-2)= -2/-2= 1

Now we want to know the m . That is by inserting a point in the equation . y=kx+m.

so I'll pick (0,3)

3=1×0+m

m=3

Try with another one to see if you get the same answer.

this time I'll pick (-2,5)

5=1×-2+m

m=3

We can try with (2,5) so that it get used too.

5=1×2+m

m=3

The right equation will therefor be

y=1x+3

Answer:

y=|x|+3

Step-by-step explanation:

ACCESS MORE
EDU ACCESS
Universidad de Mexico